2015
DOI: 10.1590/abd1806-4841.20153672
|View full text |Cite
|
Sign up to set email alerts
|

New drugs, new challenges for dermatologists: mucocutaneous ulcers secondary to everolimus

Abstract: Everolimus, a mammalian target of rapamycin inhibitor, is an emerging drug, which is being increasingly applied in oncology and solid organ transplantation. Oral ulcers are a frequent side effect associated with this immunosupressor. We report the case of a renal transplant recipient who developed disfiguring oral and perianal ulcers secondary to everolimus's toxicity. This is probably the first report of perianal involvement. Dermatologists need to be aware of the potential mucocutaneous adverse effects relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…3,5,8,9 We identified only one case report describing oral and perianal ulcers due to mTOR inhibitor therapy in a 38-year-old HIV-positive kidney transplant patient. 10 This patient presented high serum levels of everolimus 11.7 ng/mL (target area 3-8 ng/mL) and ulcers that healed only 40 days after everolimus discontinuation. In both ours and that case, no common pathogen was found to be responsible for the ongoing ulceration, and ulcer histopathology in both patients revealed non-specific ulcers, with scarce inflammatory lymphocytic infiltrates and no signs of an acute vasculitis or malignancy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…3,5,8,9 We identified only one case report describing oral and perianal ulcers due to mTOR inhibitor therapy in a 38-year-old HIV-positive kidney transplant patient. 10 This patient presented high serum levels of everolimus 11.7 ng/mL (target area 3-8 ng/mL) and ulcers that healed only 40 days after everolimus discontinuation. In both ours and that case, no common pathogen was found to be responsible for the ongoing ulceration, and ulcer histopathology in both patients revealed non-specific ulcers, with scarce inflammatory lymphocytic infiltrates and no signs of an acute vasculitis or malignancy.…”
Section: Discussionmentioning
confidence: 84%
“…We identified only one case report describing oral and perianal ulcers due to mTOR inhibitor therapy in a 38‐year‐old HIV‐positive kidney transplant patient . This patient presented high serum levels of everolimus 11.7 ng/mL (target area 3‐8 ng/mL) and ulcers that healed only 40 days after everolimus discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that one-third of patients converted to sirolimus experienced aphthous-type mouth ulcers that resolved over the course of the first 2 weeks with dose adjustment to the lower end of the target range, although three patients developed coincidental herpes simplex [68]. Everolimus is also associated with mouth ulcers [69,70] and perianal ulcers [70,71]. It is often dose-related, especially in those on steroid-free immunosuppression and after conversion from CNIs.…”
Section: Mouth Ulcersmentioning
confidence: 99%